A simple, low-cost CVD route to high-quality CH3NH3PbI3 perovskite thin films. Issue 39 (17th September 2015) - Chen, Shuqun; Briscoe, Joe; Shi, Yi; Chen, Kan; Wilson, Rory M.; Dunn, Steve; Binions, Russell
Abstract : Perovskite film formation via a sequential two-step aerosol-assisted chemical vapour deposition process. Abstract : Uniform CH3 NH3 PbI3 perovskite thin films with high phase purity and micron-sized pinhole-free grains have been successfully synthesised on fluorine-doped tin oxide (FTO) glass substrates using a novel two-step sequential aerosol-assisted chemical vapour deposition (AACVD) process.